Only behavioral but not self-report measures of speech perception correlate with cognitive abilities - Heinrich, Antje; Henshaw, Helen; Ferguson, Melanie A. (Frontiers Media, 2016)
Good speech perception and communication skills in everyday life are crucial for participation and well-being, and are therefore an overarching aim of auditory rehabilitation. Both behavioral and self-report measures can be used to assess these skills. However, correlations between behavioral and self-report speech perception measures are often low. One possible explanation is that there is a mismatch between the specific situations used in the assessment of these skills in each method, and a more careful matching across situations might improve consistency of results. The role that cognition plays in specific speech situations may also be important for understanding communication, as speech perception tests vary in their cognitive demands. In this study, the role of executive function, working memory (WM) and attention in behavioral and self-report measures of speech perception was investigated. Thirty existing hearing aid users with mild-to-moderate hearing loss aged between 50 and 74 years completed a behavioral test battery with speech perception tests ranging from phoneme discrimination in modulated noise (easy) to words in multi-talker babble (medium) and keyword perception in a carrier sentence against a distractor voice (difficult). In addition, a self-report measure of aided communication, residual disability from the Glasgow Hearing Aid Benefit Profile, was obtained. Correlations between speech perception tests and self-report measures were higher when specific speech situations across both were matched. Cognition correlated with behavioral speech perception test results but not with self-report. Only the most difficult speech perception test, keyword perception in a carrier sentence with a competing distractor voice, engaged executive functions in addition to WM. In conclusion, any relationship between behavioral and self-report speech perception is not mediated by a shared correlation with cognition.